The Relevance of Regional Anesthesia in Orthopaedic Surgery: Advantages, disadvantages and challenges. (International Journal of Medical and Surgical Sciences, 2018)
The relevance of regional anaesthesia in orthopaedic surgery cannot be overemphasized because it has aided reduction in intra-operative and post-operative pain which has always been a challenge in surgical practice. It also reduces the risk of haemorrhage and infection. Though there are complications associated with regional anaesthesia, these complications are rare and can be anticipated; thus prompt intervention measures can be instituted. The outcome of every surgical procedure takes into consideration the risks and benefit of the method, and hence, since the benefits of regional anaesthesia in orthopaedic surgery outweighs the risks, it is highly recommended. Regional anaesthesia is of great importance in orthopaedic surgery because it offers continuous but controlled analgesia. It induces hypotension which leads to a reduction in blood loss during operation. It allows early recovery and ambulation of patients, thus reducing the risks associated with prolonged bed stay, which may, in turn, affect the overall outcome of surgery. This review aims to highlight the advantages and challenges of regional anaesthesia in orthopaedic surgery.